Synergistic Fire Resistance of Nanobrick Wall Coated 3D Printed Photopolymer Lattices - Kolibaba, Thomas J.; Iverson, Ethan T.; Legendre, Hudson; Higgins, Callie I.; Buck, Zachary N.; Weeks, Timothy S.; Grunlan, Jaime C.; Killgore, Jason P. (ACS applied materials & interfaces, 2023)
Photopolymer additive manufacturing has become the subject of widespread interest in recent years due to its capacity to enable fabrication of difficult geometries that are impossible to build with traditional manufacturing methods. The flammability of photopolymer resin materials and the lattice structures enabled by 3D printing is a barrier to widespread adoption that has not yet been adequately addressed. Here, a water-based nanobrick wall coating is deposited on 3D printed parts with simple (i.e., dense solid) or complex (i.e., lattice) geometries. When subject to flammability testing, the printed parts exhibit no melt dripping and a propensity toward failure at the print layer interfaces. Moving from a simple solid geometry to a latticed geometry leads to reduced time to failure during flammability testing. For nonlatticed parts, the coating provides negligible improvement in fire resistance, but coating of the latticed structures significantly increases time to failure by up to ≈340% compared to the uncoated lattice. The synergistic effect of coating and latticing is attributed to the lattice structures’ increased surface area to volume ratio, allowing for an increased coating:photopolymer ratio and the ability of the lattice to better accommodate thermal expansion strains. Overall, nanobrick wall coated lattices can serve as metamaterials to increase applications of polymer additive manufacturing in extreme environments.